Small nucleolar RNA SNORD13H suppresses tumor progression via FBL-dependent 2′-O-methylation in hepatocellular carcinoma - Minglu Zhang; Minglu Zhang; Minglu Zhang; Minglu Zhang; Jianbo He; Jianbo He; Jianbo He; Jianbo He; Rao Fu; Rao Fu; Rao Fu; Rao Fu; et al. (Frontiers in Genetics)
IntroductionSmall nucleolar RNA (snoRNA) mediates RNA modifications, including 2′-O-methylation (Nm) and pseudouridine (Ψ), which has been proven to impact tumor progression. However, the role of snoRNA in the epigenetics of tumors remains poorly understood due to the lack of sufficiently effective experimental methods to identify snoRNA targets. Here, we identified SNORD13H, a C/D box snoRNA, as being downregulated in hepatocellular carcinoma (HCC), and its low expression was associated with HCC development.MethodsTo elucidate specific roles of SNORD13H in HCC, we used a comprehensive array of methodologies, including flow cytometry, xenograft mouse model, reverse transcription at low dNTP concentration followed by PCR (RTL-P) assay, and surface sensing of translation (SUnSET) assay.ResultsIn this study, we first demonstrated that reduced SNORD13H serves as a biomarker for HCC, facilitating cellular proliferation. SNORD13H mediates 2′-O-methylations of 18S rRNA and RAS mRNA, thereby enhancing translation efficiency and regulating RAS protein levels in HCC. The diminution of SNORD13H activates the RAS pathway, contributing to the progression of HCC.DiscussionOur study establishes SNORD13H as a dual-function regulator in HCC progression. Furthermore, our findings indicate that SNORD13H is detectable in plasma, highlighting its potential utility in tumor screening.